Prevalence of Risk for Orthorexia in Athletes Using the ORTO-15 Questionnaire: A Systematic Mini-Review - Paludo, Ana Carolina; Magatão, Marina; Martins, Hilana Rickli Fiuza; Martins, Marcos Vinícius Soares; Kumstát, Michal (Frontiers in Psychology, 2022)
The article aims to summarize the literature about the profile of risk of orthorexia in athletes using the ORTO-15 questionnaire. The search was performed at PubMed, Embase, Web of Science, and Sport Discus databases, using the terms “orthorexia” AND “athletes” with the respective entry terms. A multistage process of selection followed the PRISMA 2020 recommendation. A total of 688 articles were identified, and 67 studies were available for the final process. The prevalence of risk for orthorexia was assessed by the articles by the ORTO-15 questionnaire and ranged between 3840 to 35 points. One article with ballet dancers presented the highest score of risk of orthorexia (40.1±3.72 points). The comparison between male and female athletes and, athletes and non-athletes was not significant in he 6 out of 7 articles. In conclusion, the review highlights that athletes from different sports, included in the review, do not present a risk of orthorexia nervosa considering the cut-off of 40 points, but not 35 points. Attention should be given to ballet dancers, who seem to be more vulnerable to the risk of orthorexia. Also, athletes present the same orthorexic behavior compared to non-athletes, demonstrating that orthorexia is an issue that needs to be considered in the general population. Moreover, a special focus should be given on the ORTO-15 questionnaire, about the sensitivity to diagnose the prevalence of orthorexia, especially in athletes.